Deciphering structure and aggregation in asphaltenes: hypothesis-driven design and development of synthetic model compounds. (6th July 2021) - Scott, David E.; Schulze, Matthias; Stryker, Jeffrey M.; Tykwinski, Rik R.
Abstract : This review describes the design and synthesis of compounds that are functionalized to mimic the physical and chemical behavior of asphaltenes. The constructive interplay between synthetic compounds and modern analytical techniques is highlighted. Abstract : Asphaltenes comprise the heaviest and least understood fraction of crude petroleum. The asphaltenes are a diverse and complex mixture of organic and organometallic molecules in which most of the molecular constituents are tightly aggregated into more complicated suprastructures. The bulk properties of asphaltenes arise from a broad range of polycyclic aromatics, heteroatoms, and polar functional groups. Despite much analytical effort, the precise molecular architectures of the material remain unresolved. To understand asphaltene characteristics and reactivity, the field has turned to synthetic model compounds that mirror asphaltene structure, aggregation behavior, and thermal chemistry, including the nucleation of coke. Historically, molecular asphaltene modeling was limited to commercial compounds, offering little illumination and few opportunities for hypothesis-driven research. More recently, however, rational molecular design and modern organic synthesis have started to impact this area. This review provides an overview of commercially available model compounds but is principally focused on the design and synthesis of structurally advanced and appropriately functionalized compounds to mimic the physical and chemical behavior of asphaltenes. Efforts to model asphaltene aggregation are briefly discussed, and a prognosis for the field is offered. A referenced tabulation of the synthetic compounds reported to date is provided.